The Effect of English Subtitle in Movies to Improve Students’ Vocabulary in Grade 8 of SMPN 2 Airmadidi - Wijaya, Kairin; Salainti, Engelina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In today's interconnected world, being skilled in English is incredibly important. It opens up better job opportunities, and wider educational options, and allows participation in the global community. Therefore, inspiring students to learn English is crucial to showing them how it relates to their everyday lives. This study aims to determine the effect of English subtitles of movies on the vocabulary development of 8th-grade students in SMP Negeri 2 Airmadidi. This study adopted a preliminary experiment method. Thirty-two students participated in this targeted study. Subtitled films served as a medium to improve students' vocabulary acquisition, and vocabulary tests served as research tools. Researchers collected data through pretests, treatments, and posttests. Data were statistically analyzed and quantitatively described using SPSS 22 Edition. This study found that the mean post-test score was higher than the pre-test score (5.69 < 8.43). Also, the value of t-count is greater than the value of t-table. The results of students' scores on the post-test were higher than those on the comparison test, demonstrating the effectiveness of the treatment in improving learners' vocabulary acquisition. In summary, the use of subtitled films significantly improves students' vocabulary acquisition. This study strongly highlights that others are imaginatively exploring the use of film for a variety of abilities.